T cell-targeting nanoparticles focus delivery of immunotherapy to improve antitumor immunity. Issue 1 (December 2017) - Schmid, Daniela; Park, Chun; Hartl, Christina; Subedi, Nikita; Cartwright, Adam; Puerto, Regina; Zheng, Yiran; Maiarana, James; Freeman, Gordon; Wucherpfennig, Kai; Irvine, Darrell; Goldberg, Michael
Abstract Targeted delivery of compounds to particular cell subsets can enhance therapeutic index by concentrating their action on the cells of interest. Because attempts to target tumors directly have yielded limited benefit, we instead target endogenous immune cell subsets in the circulation that can migrate actively into tumors. We describe antibody-targeted nanoparticles that bind to CD8+ T cells in the blood, lymphoid tissues, and tumors of mice. PD-1+ T cells are successfully targeted in the circulation and tumor. The delivery of an inhibitor of TGFβ signaling to PD-1-expressing cells extends the survival of tumor-bearing mice, whereas free drugs have no effect at such doses. This modular platform also enables PD-1-targeted delivery of a TLR7/8 agonist to the tumor microenvironment, increasing the proportion of tumor-infiltrating CD8+ T cells and sensitizing tumors to subsequent anti-PD-1. Targeted delivery of immunotherapy to defined subsets of endogenous leukocytes may be superior to administration of free drugs. Targeted delivery of immunomodulatory compounds to defined subsets of endogenous immune cells may improve the efficacy of combination immunotherapies. Here, the authors use PD-1-targeting nanoparticles containing a TGFβ inhibitor or a TLR7/8 agonist to deliver these payloads to T cells or via T cells to the tumor microenvironment, respectively, leading to anti-tumor efficacy in vivo.